108k views
3 votes
Someone please solve this

Someone please solve this-example-1
User Bdart
by
4.8k points

2 Answers

4 votes

Answer:

f(-2)=12

Explanation:

We are given:

f(x)=x^2 - x^3

We are told to find f(-2). We need to find f(x) when x is equal to -2. Therefore, we can substitute -2 in for each x.

f(-2)= (-2)^2 - (-2)^3

Evaluate the exponent -2^2 .

-2^2= -2 * -2= 4

f(-2)= 4- (-2)^3

Evaluate the exponent -2^3

-2^3= -2* -2*-2= -8

f(-2)= 4- -8

f(-2)= 4+8

f(-2) =12

f(-2) is equal to 12, therefore D is correct.

User Biswajit Chopdar
by
4.9k points
3 votes

Answer:

12

Explanation:

f(x) = x^2 - x^3

Let x=-2

f(-2) = (-2)^2 - (-2)^3

= 4 - (-8)

= 4+8

= 12

User Jason Gritman
by
5.0k points